Comparative evaluation of force decay pattern in orthodontic active tiebacks exposed to five different mouth rinses: An in vitro Study - Amir Hossein Mirhashemi; Atefe Saffar Shahroudi; Keyvan Shahpoorzadeh; Niloofar Habibi Khameneh (Tabriz University of Medical Sciences, 2020)
Background. This study compared the force decay pattern of two different orthodontic active tiebacks (ATBs) exposed to five different commercially available mouth rinses. Methods. In this in vitro study, 90 transparent ATBs and 90 gray ATBs were divided into six groups; one was the control group, and the others were exposed to one of these mouth rinses twice a day for 60 seconds: Listerine, chlorhexidine, Orthokin, Persica, and fluoride. The initial force of each ATB was 250 g at a 24-mm extension. The force of ATBs was measured on days 1, 7, 14, and 28 using a digital gauge. Results. The highest percentage of force loss was observed between days 14 and 28 (P<0.05). At the end of the study, the Persica group exhibited the highest force degradation in both ATB types. In the transparent ATBs, it was followed by Orthokin, Listerine, fluoride, chlorhexidine, and control groups, respectively. In the gray ATBs, Orthokin, chlorhexidine, control, Listerine, and fluoride groups exhibited the highest force decay in descending order. In some groups, the differences between transparent and gray ATBs were significant. In the control group, the force of transparent ATB was significantly higher than gray ones on days 7 and 14 but not significantly after four weeks. Conclusion. ATBs' force degradation could be exacerbated by the use of some mouth rinses. There were some differences between force relaxation patterns of transparent and gray ATBs. The data could be beneficial in choosing appropriate O-rings for making ATBs.